Murder in a Cape cottage - Day, Maddie (Day, Maddie. Cozy Capers Book Group mystery., 2022)
"It's the day after Christmas, following a wicked-busy time of year for Mac's bike shop. It's just as well her Cozy Capers Book Group's new pick is a nerve-soothing coloring book mystery, especially when she has last-minute wedding planning to do. But all pre-wedding jitters fade into the background when Mac and her fiancé, Tim, begin a cottage renovation project and open up a wall to find a skeleton--sitting on a stool, dressed in an old-fashioned bridal gown"--